Otomatisasi Pengering Lada Menggunakan Sistem Pengayakan Berbasis Efek Rumah Kaca: Otomatisasi Pengering Lada Menggunakan Sistem Pengayakan Berbasis Efek Rumah Kaca - Risty Jayanti Yuniar; Himawan Wicaksono; Muhammad Mahdev Fiqihiyah; Rizcky Gandarrityaz; Fitri (LPPM ITK, 2026)
The pepper drying process is generally carried out conventionally under inefficient sunlight and is dependent on the weather. This study aims to analyze the performance of an automatic sieving system in a greenhouse-based pepper dryer that uses solar panels as an energy source. The main innovation of this study is the implementation of an automatic sieving mechanism to ensure even heat distribution during the drying process. The system is controlled by an Arduino Uno microcontroller with input from DHT22 sensors for temperature and humidity, and a load cell to detect weight loss of the material. A servo motor is used to move the sieve at certain intervals. Tests were conducted under two conditions, namely with and without automatic sieving, using a 60 W incandescent lamp at an average temperature of 55°C. The results showed that the automatic sieving system accelerated the drying time by up to 1 hour and 30 minutes faster than the static system. 100 grams of wet pepper was successfully dried to 75.88 grams in 7 hours, with a water content reduction of approximately 24%. These results indicate that the automatic sieving system effectively increases heat transfer efficiency and accelerates the drying process without additional external electrical energy.